Cancer cell membrane-coated C-TiO2 hollow nanoshells for combined sonodynamic and hypoxia-activated chemotherapy. (15th October 2022) - Ning, Shipeng; Dai, Xingliang; Tang, Weiwei; Guo, Qinglong; Lyu, Meng; Zhu, Daoming; Zhang, Wei; Qian, Haisheng; Yao, Xiaxi; Wang, Xianwen
Abstract: Sonodynamic therapy (SDT) is a promising strategy for tumor treatment that satisfies all requirements of penetrating deep-seated tissues without causing additional trauma. However, the hypoxic tumor microenvironment impairs the therapeutic effect of SDT. The synergistic treatment of oxygen concentration-dependent SDT and bio-reductive therapy has been proven to be an effective approach to improve the therapeutic efficiency of SDT by exploiting tumor hypoxia. Herein, a biomimetic drug delivery system (C-TiO2 /TPZ@CM) was successfully synthesized for combined SDT and hypoxia-activated chemotherapy, which was composed of tirapazamine (TPZ)-loaded C-TiO2 hollow nanoshells (HNSs) as the inner cores and cancer cell membrane (CM) as the outer shells. C-TiO2 HNSs coated with CM achieved tumor targeting via homologous binding. C-TiO2 @CM as a nanocarrier loaded with TPZ in the presence of the trapping ability of CM and the special cavity structure of C-TiO2 HNSs. Moreover, C-TiO2 HNSs as sonosensitizers killed cancer cells under ultrasound (US) irradiation. Oxygen depletion during SDT induced a hypoxic environment in the tumor to activate the killing effect of co-delivered TPZ, thereby obtaining satisfactory synergistic therapeutic effects. In addition, C-TiO2 @CM exhibited remarkable biocompatibility without manifest damage and toxicity to the blood and major organs of the mice. The study highlighted that C-TiO2 /TPZ@CM served as a powerful biomimetic drug delivery system for effective SDT by exploiting tumor hypoxia. Statement of significance: C-TiO2 @CM achieved tumor targeting via homologous binding. C-TiO2 hollow nanoshells could be used as a sonosensitizer and drug carrier for synergistic SDT and hypoxia-activated chemotherapy. C-TiO2 /TPZ@CM showed no obvious toxicity under the injection dose. Graphical abstract: Image, graphical abstract